Nanomaterials in drug delivery, imaging, and tissue engineering - Tiwari, Atul; Tiwari, Atul (Hoboken, New Jersey : John Wiley & Sons, 2013)
'Nanoscopic therapeutic systems incorporate therapeutic agents, molecular targeting and diagnostic imaging capabilities and are emerging as the next generation of multifarious nanomedicine to improve the therapeutic outcome including chemo and translational therapy. This reference work is one of the first to cover Nanotheragnostics which is the new edge of nanomedicine combining both diagnostic and therapeutic elements at nano level.This large multidisciplinary reference work is has four main parts: Biocompatible Nanomaterials; Nanomedicine: Drug Gene and Cell Delivery; Multi-functional Nanocarrier: Diagnosis, Imaging and Treatment; Tissue Engineering/Regenerative Medicine'--
'This book is written for a large readership including university students and researchers from diverse backgrounds such as chemistry, materials science, physics, pharmacy, medical science, and biomedical engineering'--
Part I: Biomedical nanomaterials -- Nanoemulsions : preparation, stability and application in biosciences / Thomas Delmas, Nicolas Atrux-Tallau, Mathieu Goutayer ...[et al.] -- Multifunctional polymeric nanostructures for therapy and diagnosis / Angel Contreras-Garc, Emilio Bucio -- Carbon nanotubes : nanotoxicity testing and bioapplications / R. Sharma, S. Kwon -- Part II: Advanced nanomedicine -- Discrete metalla-assemblies as drug delivery vectors / Bruno Therrien -- Nanomaterials for management of lung disorders and drug delivery / Jyothi U. Menon, Aniket Wadajkar, Zhiwei Xie ...[et al.] -- Nano-sized calcium phosphate (CaP) carriers for non-viral gene/drug delivery / Donghyun Lee, Geunseon Ahn, Prashant N. Kumta -- Part III: Nanotheragnostics -- Organics modified mesoporous silica for controlled drug delivery systems / Jingke Fu, Yang Zhao, Yingchun Zhu ...[et al.] -- Responsive polymer-inorganic hybrid nanogels for optical sensing, imaging, and drug delivery / Weitai Wu, Shuiquin Zhou -- Core/shell nanoparticles for drug delivery and diagnosis / Hwanbum Lee, Jae Yeon Kim, Eun Hee Lee ...[et al.] -- Dendrimer nanoparticles and their applications in biomedicine / Arghya Paul, Wei Shao, Tom J. Burdon ...[et al.] -- Theranostic nanoparticles for cancer imaging and therapy / Mami Murakami, Mark J. Ernsting ...[et al.] -- Part IV: Nanoscaffolds technology -- Nanostructure polymers in function generating substitute and organ transplants / S. K. Shulka -- Electrospun nanofiber for three dimensional cell culture / Yashpal Sharma, Ashutosh Tiwari, Hisatoshi Kobayashi ...[et al.] -- Magnetic nanoparticles in tissue regeneration / Anuj Tripathi, Jose Savio Melo, Stanislaus Francis D'Souza -- Core-sheath fibers for regenerative medecine / Rajesh Vasita, Fabrizio Gelain.
Includes bibliographical references and index.
Keywords: Diagnostic imaging; Drug delivery systems; Tissue Engineering; Biomedical materials; Drug delivery systems; Tissue engineering